The Mediating Role of Organizational Citizenship Behavior in the Relationship Between Job Satisfaction and Organizational Performance: Evidence from Nepal’s Hospitality Sector - Blown, Basanta (Nepalese Journal of Hospitality and Tourism Management, 2026)
This study aims to investigate the relationship between job satisfaction and organizational performance, with the mediation effect of organizational citizenship behavior. This study employed a crosssectional quantitative design to examine both the direct and indirect relationships among the study variables using the data gathered from 427 employees working in hospitality sector. Strong positive correlation between job satisfaction, organizational citizenship behavior and organizational citizenship behavior were found in the correlation results. Regression analysis also indicated that organizational citizenship behavior and organizational performance are significantly predicted by job satisfaction. Furthermore, the PLS-SEM mediation analysis showed that the relationship between job satisfaction and organizational performance is partially mediated by organizational citizenship behavior. This finding suggests that employees who are satisfied are more likely to participate in voluntary, extra-role activities, that improve the effectiveness of the organization. By empirically confirming the mediating role of organizational citizenship behavior in the relationship between job satisfaction and organizational performance within the context of hospitality sector of developing country, this study contributes to the existing literatures. The results also offer significant managerial recommendation, indicating that strategies to enhance job satisfaction on employees can encourage discretionary citizenship behaviors that eventually improve organizational performance. The findings offer meaningful insights for researchers and practitioners of hospitality sector seeking to understand the behavioral pathways to enhance organizational performance.